The Middle East in modern world history - Tucker, Ernest S. 1961- (Routledge, Taylor & Francis Group, 2019)
The Middle East in Modern World History examines how global trends over the last 200 years have shaped the Middle East and how these trends were affected by the region's development. This edition extends coverage to the present day and includes more thematic and interpretive discussion on the impact of global migration and the evolution of the roles of women. It also provides more theoretical insights into current historical research and recent developments in the region. Clearly written and supported by maps, images, discussion questions, further reading, a chronology and glossary, it is the ideal textbook for all students of the history of the modern Middle East within a global context